Chondrosarcoma of the Upper Extremity of the Humerus: A Case Report - Mouhsine, Abdelilah; Sallahi, Hicham; Belkouch, Ahmed; Atmane, El Mehdi; Rokhssi, Redouane; Berrada, Youssef; Koulali, Khalid; Belyamani, Lahcen; ElFikri, Abdelghani; Mahfoudi, Mbarek (Journal of Diagnostics, 2014)
Chondrosarcomas are frequent bone tumors, just after osteosarcomas, they represent 11 to 22% of all bone tumors. Proximal humerus localization occurs in about 9% of cases, the clinical picture is variable, imagery helps to establish the diagnosis, to give an exact lesion assessment and to guide therapeutic attitude and post treatment control. Confirmation is set by histology. We highlight through this case presentation clinical and radiological aspects of these tumors.